PENGARUH PERPUTARAN MODAL KERJA, PERPUTARAN KAS, DAN PERPUTARAN PERSEDIAAN TERHADAP PROFITABILITAS PADA PERUSAHAAN OTOMOTIF DI BURSA EFEK INDONESIA TAHUN 2017-2019 - Saryanti, Novina (Soetomo Accounting Review, 2022)
The purpose of this study was to determine the effect of working capital turnover, cash turnover, and inventory turnover on profitability. Profitability is used as a measure of how the company generates profits from its operations. The main goal of the company is to get the maximum possible profit. The higher the profit earned by the company reflects the effectiveness of the company in carrying out its operational activities so that it can increase profits optimally. This study discusses working capital turnover, cash turnover, and inventory turnover on profitability in automotive companies listed on the Indonesian stock exchange in 2017-2019.Samples were taken based on certain criteria or purposive sampling. The results of this study indicate that the results of working capital turnover have an effect on profitability, while cash loading and inventory turnover have no effect on profitability.